Phenols, Flavors, and the Mediterranean Diet. (4th June 2020) - Issaoui, Manel; Delgado, Amélia Martins; Caruso, Giorgia; Micali, Maria; Barbera, Marcella; Atrous, Hager; Ouslati, Amira; Chammem, Nadia
Abstract: Phenols or phenolics are a class of compounds that have one or more hydroxyl groups attached to a 6-carbon aromatic ring, they occur as plant secondary metabolites, having in common the antioxidant activity. Their average daily intake varies widely around the world. Many researchers consider coffee, tea, wine, cocoa products, fruits and vegetables as the main sources of polyphenols in different diets. However, spices and culinary herbs have been referred to as the foods richest in polyphenols. Despite spices and culinary herbs are used in small amounts as seasonings, their contribution to the dietary supply of phytonutrients should not be disregarded. A diet rich in a variety of polyphenols (and other phytonutrients) has potential health benefits, namely in the prevention of chronic diseases and cancer. In addition, flavor and color are the most important factors for the selection of food by consumers. A multitude of endogenous food compounds, including phenolics, are involved in food flavor. The presence of phenolic compounds in the food matrix has been mainly associated with the perception of bitter taste and tactile sensation of astringency. However, these compounds can also impact the color and aroma notes of fruits and vegetables. Thus, understanding the sensory impact of these substances and relationships with consumers' approaches towards phenolic-rich fruits and vegetables may help find strategies to increase the consumption of such foods. A well-known example of a tasty, healthy and sustainable dietary model is the Mediterranean Diet. In this study, we summarize the dietary intake of some polyphenols from different dietary patterns around the world and the contribution of natural phenolic compounds to the flavor of food and beverages, in particularly those associated to the Mediterranean Diet.